Single port robotic platform and toolbox: What is new - Angelo Orsini; Gabriele Bignante; Francesco Lasorsa; Sofia S. Rossetti; Francesco Berardinelli; Daniel Roadman; Carol Feng; Riccardo Autorino (Urology Video Journal)
Introduction: The DaVinci Single Port™ (SP) system is a recent innovation in urologic surgery, initially evaluated in cadaveric models for various procedures. Following successful clinical trials and FDA approval in 2018, the system received the CE mark in January 2024, enabling its use in Europe. This paper and the accompanying video provide an overview of the SP system, highlighting its instruments and tools. Materials and Methods: The video includes footage from various single-port (SP) robotic urologic procedures, supplemented by additional recordings in the operating room to illustrate technical and operational details. The key aspects of the SP system are highlighted through voice-over commentary, detailing the setup of the operating room and the instruments used. Instruments and Procedures: The SP system consists of a surgeon console and a patient-side cart. The console features a 3D-HD screen and a Virtual Navigator for real-time instrument tracking. The patient-side cart has a single arm with four instrument drives controlling a 12 × 8 mm articulating camera and three 6-mm double-jointed articulating endowristed instruments. These instruments pass through an entry guide, comprising an oval lumen for the scope and three circular lumens for the instruments. The SP kit includes a short entry guide, access port, and wound retractor, facilitating instrument rotation and insufflation. The Custom Remote Center (CRC) allows for precise instrument control, minimizing tissue damage. Available instruments include Cadiere forceps, round tooth retractor, clip applier, needle driver, bipolar forceps, monopolar scissors, cautery tools, and the Remotely Operated Suction Irrigation System (ROSI). Intraoperative ultrasound can also be used. Camera control modes and the relocation feature enhance the surgeon's field of vision and workspace. The bedside assistant plays a crucial role in instrument exchange, suction, and applying vascular clips. Conclusion: This video guide provides a detailed overview of the SP robotic platform and its accessories, offering practical insights for implementing the SP system in urologic surgical practice.